Analisis Kreativitas Belajar Siswa SMK Swasta Pelita Bulu Cina - Zulfi Aulia; Zulham Siregar; Yusda Novianti (Badan Penerbit STIEPARI Press, 2025)
Consumable goods are household waste that is no longer used, consumable goods can include plastic bottles, cardboard or household equipment that is no longer used. The use of consumable media for vocational school students in this research is to increase student creativity. This research aims to determine: (1) The process of using consumables as a medium for increasing the creativity of class 10 students in Indonesian history subjects at SMK Pelita Bulu Cina (2) obstacles in using consumables as a medium for increasing the creativity of class 10 students in the field of learning. Indonesian history lessons at SMK Pelita Bulu Cina (3) Supporting factors in the use of consumables as a medium for increasing the creativity of grade 10 students in Indonesian history subjects at SMK Pelita Bulu Cina. This research method uses descriptive qualitative research, data analysis is carried out using descriptive techniques. The research results show that the activity of utilizing consumables through Indonesian history subjects at SMK Pelita Bulu Cina can be used as a medium to increase student creativity both motorically and cognitively and students are able to develop a work according to their own thoughts and imagination.